Management and treatment of long COVID symptoms in general practices: An online-based survey - Schrimpf, Anne; Braesigk, Annett; Lippmann, Stefan; Bleckwenn, Markus (Frontiers in Public Health, 2022)
Independent from initial severity, many patients develop persistent symptoms after infection with SARS-CoV-2, described as long COVID syndrome. Most of these patients are treated by general practitioners (GPs). As evidence-based treatment recommendations are still sparse, GPs must make their therapy decisions under uncertainty. We investigated 1) the most frequently observed long COVID symptoms in general practices and 2) GPs’ applied treatment and rehabilitation plans for these symptoms. In total, 143 German GPs participated in an online-based survey between 05/2021-07/2021. We found that each GP practice was treating on average 12 patients with long COVID symptoms. Most frequently seen symptoms were fatigue and reduced performance. Current therapy options were rated as poor and loss of smell and taste, fatigue, or lack of concentration were perceived to be especially difficult to treat. The use of drug and non-drug therapies and specialist referrals focused primarily on physiological and less on psychosomatic/psychological rehabilitation and followed guidelines of similar conditions. Our results provide first insights into how GPs approach a newly emerging condition in the absence of guidelines, evidence-based recommendations, or approved therapies, and might inform about GP preparedness in future pandemics. Our results also emphasize a gap between the current knowledge of the long COVID manifestation and knowledge about effective rehabilitation.